Rethinking Institutional Secularization as an (Im)possible "Policy" - Ezequiel Gomez Caride (Arizona State University, 2015)
The paper analyzes through a genealogical discourse analysis how religion as a cultural practice escapes into the borders of state institutions. While most studies about secularization focus on institutional aspects, such approaches tend to link state secularist policies with cultural secularization. This essay argues that state promotion of religious institutional secularist policies needs to be rethought. The institutionalization of republicanism in Argentina exemplifies this problem. In order to shape a secular Argentinean citizen the government promoted an array of secularist policies (1860-1910). The article aims to problematize such linear historical account by showing how Catholic religious principles became part of the "secular" Argentinean citizen. In fact, religious connotations such as salvific narratives or dogmatic qualities were reenacted in seemingly secular state discursive spaces. Nowadays, several states are enacting secularist state policies to ban nonwestern religious manifestations from public spaces such as schools. In unraveling the Argentinean processes, the article aspires to highlight the impossibilities of banning religion from the narratives that shape the republican citizen.